Impact of Credit Performance on the Profitability of Nepalese Development Banks - Kandel, Madan (Journal of Nepalese Management Academia, 2024)
This study investigates the relationship between credit performance and profitability in Nepalese development banks. Using data from 10 development banks over a 5-year period (2018-2023), we examine the impact of Credit to Deposit Ratio (CDR), Non-Performing Loan Ratio (NPLR), and Capital Adequacy Ratio (CAR) on Return on Assets (ROA) and Return on Equity (ROE). Results show that CDR has a positive effect on profitability, while NPLR has a significant negative impact. Additionally, CAR positively influences both ROA and ROE. These findings highlight the importance of maintaining a robust capital buffer and managing credit risk effectively to enhance profitability in development banks. The study provides useful insights for bank managers and policymakers in Nepal and other emerging economies.